Left subclavian arterioesophageal fistula induced by chicken bone with upper gastrointestinal hemorrhage and unexpected death: Report of a case - Vichan Peonim (2018)
Left subclavian arterioesophageal fistula resulting from chicken bone ingestion is a rare occurrence. The authors report the death of a 42-year-old Thai female with mental retardation who presented to the hospital with severe hematemesis and arrested. Death occurred about 24 hours after laparotomy due to hypovolemic shock. Postmortem examination revealed a chicken bone embedded in middle part of esophagus with fistula between the esophagus and the left subclavian artery.